The skull talks back and other haunting tales - Hurston, Zora Neale (HarperCollins, 2004)
Presents illustrated adaptations of six scary stories from Zora Neale Hurston's "Every Tongue Got to Confess," a collection of tales from Florida, Alabama, and Louisiana gathered in the late 1920s.